Cheri (Miramax Home Entertainment Distributed by Buena Vista Home Entertainment, 2009)
The story of the love affair between a beautiful retired courtesan Lea, and Cheri, the son of her old colleague and rival, Madame Peloux. After six years Madame Peloux has secretly arranged a marriage between Cheri and Edmee, the daughter of another rich courtesan. As the inevitable moment of parting approaches, Lea and Cheri begin to understand, too late, how much they mean to one another.